Cyber Public Relations Diskominfo Kabupaten Klaten dalam Optimalisasi Layanan Informasi Publik - Dewi Ayu Sri Hastuti; Eny Susilowati (UIN Raden Mas Said Surakarta, 2020)
This study aims to describe the Klaten Diskominfo PR PR cyber strategy in optimizing public information services. The background of the research is the management of public information services primarily through the website of the Klaten Regency government which has not been optimal. The method used in this research is a descriptive qualitative method. The results of this study can be concluded that in optimizing the public information service owned by Diskominfo, Klaten Regency has practised a cyber PR strategy that combines 4 things as a whole, namely Strategic (has a communication design plan that is not done haphazardly. Next is Integrated (using the internet and its facilities as a means publication, this has been realized with the official website of klatenkab.go.id which is integrated with other websites underneath), Targeted (has and can reach specific target audiences, namely the Klaten community, government officials and millennial generation to generation Z), and Measurable (It has measurable results, in this case, it has clear measurement data such as the number of visits, followers (in social media), and web traffic. With the existing cyber PR strategy, it can optimize public information services managed by Klaten Diskominfo.